2017
DOI: 10.1177/1464884917692344
|View full text |Cite
|
Sign up to set email alerts
|

Journalism students’ professional identity in the making: Implications for education and practice

Abstract: Changes in journalism spurred by technological shifts and industry restructuring have left observers questioning both the nature of the profession and what educators ought to do in order to prepare aspiring journalists. Despite attempts to rethink what it means to be a journalist and the educational experience needed to prepare students, few qualitative studies have emerged that track how learners are negotiating professional values. This article does precisely that by providing a case study of how students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…You can forget journalism anyway; you'll never make it"' (2016, f_1). Apparently, our respondents were advised against pursuing the career confirming the finding that journalism students are intensely warned of the death of the industry (Williams et al, 2018). This might explain why Hanna and Sanders (2007) found that students' interest in starting a journalistic career decreases in the course of their studies.…”
Section: Job Motivations and Expectationssupporting
confidence: 77%
See 1 more Smart Citation
“…You can forget journalism anyway; you'll never make it"' (2016, f_1). Apparently, our respondents were advised against pursuing the career confirming the finding that journalism students are intensely warned of the death of the industry (Williams et al, 2018). This might explain why Hanna and Sanders (2007) found that students' interest in starting a journalistic career decreases in the course of their studies.…”
Section: Job Motivations and Expectationssupporting
confidence: 77%
“…Journalists interviewed by Goyanes and Rodríguez-Gómez (2018) were concerned that present circumstances make it increasingly difficult to reach high quality standards. Even journalism students seem to already be aware of these constraints: While they aspire to fulfil a watchdog role in society, they fear that achieving this ideal will be hampered by the constraints of ethical standards and the objectivity norm (Williams et al, 2018).…”
Section: Disillusionmentmentioning
confidence: 99%
“…Academic learning is identified as a major formative influence in the development of professional identities among student journalists (Williams, Guglietti, & Haney, 2017). Based on students' perception and industry input (Drok, 2013), "back to basics" is often projected as a preferred approach for addressing issues like fake news; however, this lacks temporal, reflexive thinking (Carlson & Lewis, 2018).…”
Section: Understanding Journalism Students' Perceptionmentioning
confidence: 99%
“…) • Actual social topics and contents (Ilgaz Büyükbaykal, 2016, etc. ) • The sexes in journalism education and practice (Alacrón Espinoza, 2015) • Journalism identity (Vukić, 2017;Williams et al, 2017) • Definition of basic concepts in journalism education (Vukić, 2017) • Cooperation between journalism and other important social systems (Newman & Drevo, 2015;Vukić, 2017, etc.) and many others.…”
Section: Higher Journalism Education Sustainability and Developmentmentioning
confidence: 99%